SISTEM INFORMASI PEMESANAN MENU MAKANAN BERBASIS WEB - Muhammad Rizki Ramadhan; Tata Sutabri (Cross-border, 2023)
he development of internet technology and mobile applications has brought us one step further in the implementation of technology in modern life. One of them is an application for obtaining goods and services in the form of online food ordering applications. In addition to being faster and more practical, online ordering is also considered more convenient, as it offers options for consumers to browse menus, food reviews, and others. The research method used is software development using the waterfall method. With the design of a web-based online food ordering application, consumers do not need to come directly when they want to order food. This application also helps the effectiveness of work time to be faster and more efficient. And can produce information that is fast, precise, and accurate because it uses the Mysql database system, so data can be connected to each other.